2002
DOI: 10.1055/s-2002-19273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C and E Supplementation on Biochemical and Ultrastructural Indices of Muscle Damage after a 21 km Run

Abstract: This study investigated whether 4 weeks of daily supplementation with 500 or 1000 mg of Vitamin C and 500 or 1000 IU of Vitamin E could modify biochemical and ultrastructural indices of muscle damage following a 21 km run. Fifteen experienced male distance runners were divided into two groups (vitamin or placebo) and received supplementation for four weeks before completing the first 21 km run in as fast a time as possible. A four-week "washout" period followed before the subjects crossed over and received the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 21 publications
6
42
2
5
Order By: Relevance
“…Elevation of plasma and erythrocyte LP in exercised basketball players and in rats was reported by some investigators. [9][10][11][12][13][14]27,28 These results support the view that enhanced oxidative stress is involved in the aetiology of erythrocyte pathophysiology.…”
Section: Discussionsupporting
confidence: 81%
“…Elevation of plasma and erythrocyte LP in exercised basketball players and in rats was reported by some investigators. [9][10][11][12][13][14]27,28 These results support the view that enhanced oxidative stress is involved in the aetiology of erythrocyte pathophysiology.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, VCE supplementation in the forced training basketball players are characterized by increased a free testosterone levels and decreased CK activities and cortisol levels. A limited number of separately VCE administrated studies in blood of forced training have been reported regarding the effects of VCE on stress marker enzymes and hormones system and LP levels [3,10,15,19]. To the best of our knowledge, the current study is the first to compare the vitamin combination with particular reference to its effects on muscle enzyme and the hormone system using levels of CK, LDH, cortisol, testosterone and hematological values in blood of forced training subjects.…”
Section: Discussionmentioning
confidence: 94%
“…However there are also conflict reports on the subjects. Recently, Dawson et al [3] reported that no significant differences were found between the VCE and placebo groups for CK levels recorded after the 21 km runs. Mastaloudis et al [10] repor-…”
Section: Effects Of Vitamin C and E Combination O N H O R M O N A L mentioning
confidence: 97%
See 1 more Smart Citation
“…Beberapa studi menyebutkan pemberian suplemen antioksidan memberikan pengaruh positif terhadap sistem antioksidan dalam tubuh setelah mengkonsumsi antioksidan single (Palazzeti et al, 2003(Palazzeti et al, dan 2004) Namun, beberapa studi menyebutkan suplementasi antioksidan yang dilakukan pada athlete mampu menjaga kesehatan optimal atlete dengan cara mencegah peningkatan kerusakan jaringan akibat stress oksidatif reaksi berantai radikal bebas dalam tubuh. Beberapa antioksidan (seperti vitamin A, E, dan C) mampu melindungi individu yang melakukan aktivitas fisik dari radikal bebas yang merusak jaringan otot selama latihan fisik (Dawson et al, 2002).…”
Section: Efek Fungsional Suplementasi Antioksidan Terhadap Latihan Fisikunclassified